RECEIVABLE ACCOUNTING TREATMENT BASED ON GOVERNMENT ACCOUNTING STANDARDS ON THE LOCAL GOVERNMENT FINANCIAL REPORT OF NGANJUK REGENCY - Ahmad Kudhori; Hamim Tohar; Nova Maulud Widodo (International Conference on Business Management and Accounting, 2022)
This research was conducted at the Regional Financial and Asset Management Agency (BPKAD) of Nganjuk Regency, having its address at Jalan Basuki Rachmad Number 1 Nganjuk. The purpose of this study was to determine the analysis of accounts receivable and the application of financial statements to BPKAD based on Government Accounting Standards. Data collection techniques are carried out by means of observation and interviews, to collect information in the form of government financial reports that have been audited by the Financial Supervisory Agency to be analyzed according to Accounting Standards for Accounts Receivable Number 6 concerning Accounting for Receivables accompanied by supporting evidence, namely documentation. The issuance of Government Regulation No. 71 of 2010 has brought significant changes in government financial reporting. These changes are set forth in the accounting policies and accounting systems that form the basis before being implemented in the presentation of financial statements. Changes in the accounting basis to the accrual basis must be carried out no later than 2016. The results of research at the Regional Financial and Asset Management Agency of Nganjuk Regency have applied the Accrual-Based Government Accounting Standards in 2015 for the preparation of financial statements consisting of: Budget Realization Report, Report on Changes in Budget Balance, Balance Sheet, Operational Report, Report on Changes in Equity, and Statement of Cash Flows. Total current assets in 2020 experienced a large increase of Rp4.032.915.127,53 obtained from the total current assets in 2020 of Rp445.230.242.894,16 minus the total current assets in 2019 of Rp441.197.327.766,63.